Impact of p53 status on TRAIL-mediated apoptotic and non-apoptotic signaling in cancer cells - Willms, Anna (PLoS One, 2019)
Due to their ability to preferentially induce cell death in tumor cells, while sparing healthy cells, TNF-related apoptosis-inducing ligand (TRAIL) and agonistic anti-TRAIL-R1 or anti-TRAIL-R2-specific antibodies are under clinical investigations for cancer-treatment. However, TRAIL-Rs may also induce signaling pathways, which result in malignant progression. TRAIL receptors are transcriptionally upregulated via wild-type p53 following radio- or chemotherapy. Nevertheless, the impact of p53 status on the expression and signaling of TRAIL-Rs is not fully understood. Therefore, we analyzed side by side apoptotic and non-apoptotic signaling induced by TRAIL or the agonistic TRAIL-R-specific antibodies Mapatumumab (anti-TRAIL-R1) and Lexatumumab (anti-TRAIL-R2) in the two isogenic colon carcinoma cell lines HCT116 p53(+/+) and p53(-/-). We found that HCT116 p53(+/+) cells were significantly more sensitive to TRAIL-R-triggering than p53(-/-) cells. Similarly, A549 lung cancer cells expressing wild-type p53 were more sensitive to TRAIL-R-mediated cell death than their derivatives with knockdown of p53. Our data demonstrate that the contribution of p53 in regulating TRAIL-R-induced apoptosis does not correlate to the levels of TRAIL-Rs at the plasma membrane, but rather to p53-mediated upregulation of Bax, favouring the mitochondrial amplification loop. Consistently, stronger caspase-9 and caspase-3 activation as well as PARP-cleavage was observed following TRAIL-R-triggering in HCT116 p53(+/+) compared to HCT116 p53(-/-) cells. Interestingly, HCT116 p53(+/+) cells showed also a more potent activation of non-canonical TRAIL-R-induced signal transduction pathways like JNK, p38 and ERK1/ERK2 than p53(-/-) cells. Likewise, these cells induced IL-8 expression in response to TRAIL, Mapatumumab or Lexatumumab significantly stronger than p53(-/-) cells. We obtained similar results in A549 cells with or without p53-knockdown and in the two isogenic colon cancer cell lines RKO p53(+/+) and p53(-/-). In both cellular systems, we could clearly demonstrate the potentiating effects of p53 on TRAIL-R-mediated IL-8 induction. In conclusion, we found that wild-type p53 increases TRAIL-R-mediated apoptosis but simultaneously augments non-apoptotic signaling.